Age of Ingenuity : Re-imagining 21st Century International Cooperation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2019)
International Monetary Fund Managing Director Christine Lagarde delivered this address at the Library of Congress as part of the Library's Henry A. Kissinger Lecture Series in Washington, D.C. on December 4, 2018.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Collaborative Leadership; Countries Breathing Space; Country; Mexican Peso; SPE; United States